Stroke Therapy Robotic Arm Using Master-slave Method - Lami, Dionisius Aurelius; Sonalitha, Elta; Subairi, Ir. (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
Stroke is a disease that can be suffered by anyone and its handling is not easy. Strok e sufferers need to undergo a therapeutic process so that the function of the limbs can be moved again, such as the feet, hands, and fingers. Based on this, a strok e therapy robot hand was built as a tool to carry out therapy for stroke sufferers. The stroke therapy robot hand consists of two parts, the gloves for the therapist and the hand frame for the sufferers. This tool uses Arduino Nano as a microcontroller base. This tool works by reading the value from the potentiometer in the therapist's hand, then the information is transmitted to the strok e therapy robot's hand via a wireless communication line using the nRF24L01 module which is then run using the Master - slave method. Th is data will drive five servo motors that are used to move the patient's fingers. From the test results show that the tool can work by calculating the movement of the finger that has moved successfully 98 out of 100 trials. This means that the success percentage of this tool is 98% with an error of 2%.